2012
DOI: 10.1002/ijc.27817
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of real time next generation sequencing of cancer genes linked to drug response: Results from a clinical trial

Abstract: The successes of targeted drugs with companion predictive biomarkers and the technological advances in gene sequencing have generated enthusiasm for evaluating personalized cancer medicine strategies using genomic profiling. We assessed the feasibility of incorporating real-time analysis of somatic mutations within exons of 19 genes into patient management. Blood, tumor biopsy and archived tumor samples were collected from 50 patients recruited from four cancer centers. Samples were analyzed using three techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 28 publications
1
62
1
Order By: Relevance
“…The tumor biopsy study evaluated whether high-throughput sequencing, accompanied by verification of results in a clinical laboratory, was feasible, could be used as a clinical tool to guide cancer therapy and would add value to the information generated by traditional genotyping methods. 37 With ethics approval from the Ontario Cancer Research Ethics Board, University of Toronto, and participating hospitals, as well as informed consent from participants, we conducted open-ended, semi-structured interviews from May 2011 to June 2012 with (i) adult patients with advanced solid malignancies enrolled in the tumor biopsy study; to enable face-to-face interviews, only patients from the three southern Ontario sites were eligible; and (ii) medical oncologist investigators involved in recruitment for the study at the three southern Ontario and two northern Ontario sites.…”
Section: Methodsmentioning
confidence: 99%
“…The tumor biopsy study evaluated whether high-throughput sequencing, accompanied by verification of results in a clinical laboratory, was feasible, could be used as a clinical tool to guide cancer therapy and would add value to the information generated by traditional genotyping methods. 37 With ethics approval from the Ontario Cancer Research Ethics Board, University of Toronto, and participating hospitals, as well as informed consent from participants, we conducted open-ended, semi-structured interviews from May 2011 to June 2012 with (i) adult patients with advanced solid malignancies enrolled in the tumor biopsy study; to enable face-to-face interviews, only patients from the three southern Ontario sites were eligible; and (ii) medical oncologist investigators involved in recruitment for the study at the three southern Ontario and two northern Ontario sites.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies showed that these technologies can be applied to the detection of somatic mutation and suggested that they can be used in clinical settings (23).…”
Section: Introductionmentioning
confidence: 99%
“…The consortium's task is far from done. Although many members are engaged in exciting translational projects (21)(22)(23), the consortium needs to focus on achieving its primary goal of generating comprehensive descriptions of genomic, transcriptomic, and epigenomic changes in 50 different tumor types to provide the comprehensive perspective that motivated the consortium from the outset. Most projects under way have generated data for only a subset of planned samples and usually only 1 or 2 of the data types that are required.…”
Section: Qualitymentioning
confidence: 99%